2022
DOI: 10.4093/dmj.2021.0115
|View full text |Cite
|
Sign up to set email alerts
|

Development of Various Diabetes Prediction Models Using Machine Learning Techniques

Abstract: Background: There are many models for predicting diabetes mellitus (DM), but their clinical implication remains vague. Therefore, we aimed to create various DM prediction models using easily accessible health screening test parameters. Methods: Two sets of variables were used to develop eight DM prediction models. One set comprised 62 easily accessible examination results of commonly used variables from a tertiary university hospital. The second set comprised 27 of the 62 variables included in the national rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Studies that developed diabetes prediction models using health checkup data generally did not consider 2-hour glucose when defining diabetes. 25 26 However, in line with previous studies, 27 28 we observed differences in prevalence depending on the definition of diabetes. Also, one meta-study suggested lowering the cutoff values for FBG and HbA1c in relation to diabetes diagnosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Studies that developed diabetes prediction models using health checkup data generally did not consider 2-hour glucose when defining diabetes. 25 26 However, in line with previous studies, 27 28 we observed differences in prevalence depending on the definition of diabetes. Also, one meta-study suggested lowering the cutoff values for FBG and HbA1c in relation to diabetes diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, in our study, no significant contribution of parental history of diabetes was observed in predicting diabetes. Also, like previous studies, 5 25 the contribution of sex to diabetes prediction was not found to be significant. Instead, the modified FDRM showed a predictive power of over 0.8 for both sexes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, because this study used data from medical examinations at university hospitals, it contained many variables. 37 Lastly, the medical check-up did not include postprandial blood glucose measurement, one of the main diagnostic criteria for diabetes. Therefore, patients with impaired glucose tolerance may have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…Third, in this study, it was difficult to identify a clear causal relationship due to the nature of the retrospective cohort study, 35,36 and since various confounding variables could not be excluded, only correlations could be estimated. However, because this study used data from medical examinations at university hospitals, it contained many variables 37 . Lastly, the medical check‐up did not include postprandial blood glucose measurement, one of the main diagnostic criteria for diabetes.…”
Section: Discussionmentioning
confidence: 99%